THE ELLIPTED SYNTACTIC COMPLEMENT (AL-MUTAʿALLAQ AL-MAḤDHUF) IN AL-ZAMAKHSHARI’S TAFSIR AL-KASHSHAF: GRAMMATICAL STRUCTURE AND RHETORICAL FUNCTION (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the phenomenon of the ellipted syntactic complement (al-mutaʿallaq al-maḥdhuf) in the Qurʾanic commentary Tafsir al-Kashshaf ʿan Ḥaqaʾiq Ghawamiḍ al-Tanzil by Jar Allah al-Zamakhshari (d. 538 AH / 1144 CE). It explores how al-Zamakhshari systematically employs his grammatical, rhetorical, and hermeneutical expertise to identify, interpret, and justify the presence of omitted syntactic elements in Qurʾanic discourse – particularly the elided governing verbs or semantic heads associated with prepositional constructions (al-jar wa al-majrur).The study situates this analytical approach within the broader intellectual framework of classical Arabic grammar by tracing the theoretical foundations of the concept of mutaʿallaq from Sibawayhi through the development of the Basran and Kufan grammatical traditions and their eventual synthesis. In doing so, it demonstrates that al-Zamakhshari not only inherits this rich grammatical legacy but also significantly refines and advances it.Through a systematic analysis of selected passages from al-Kashshaf, the article argues that syntactic ellipsis in al-Zamakhshari’s exegesis functions on multiple levels: as a grammatical necessity, a rhetorical strategy, and a hermeneutical tool. This multifaceted function enables the exegete to reconstruct the full semantic depth of Qurʾanic expressions from their condensed and rhetorically nuanced surface forms.
Keywords: al-Zamakhshari; al-Kashshaf; Qurʼanic linguistics; syntactic ellipsis; al-mutaʿallaq al-maḥdhuf; Arabic grammar; prepositional phrases; nahw; iʿrab; Muʿtazilism; Qurʼanic exegesis; rhetorical analysis